Genetic analysis of Pinna rudis L 1758 (Mollusca, Bivalvia, Pinnidae) in the Northwest Cabo Verde Islands (Central-East Atlantic) - Lopes, Evandro P.; Santos, Sarah; Xavier, Raquel; Santos, Joana L.; Cabezas, M. Pilar; Sequeira, Fernando; Santos, António M. (PeerJ, 2025)
The rough pen shell Pinna rudis Linnaeus, 1758 (family Pinnidae) is a mollusc with an Atlantic–Mediterranean distribution, typically inhabiting coarse sandy substrates. Habitat degradation is considered the primary cause of population decline, leading to the designation ‘Vulnerable’ in certain regions. In this study, we conducted a genetic analysis of populations of P. rudis from Cabo Verde and compared them with populations from the Mediterranean and Macaronesia. We based our analysis on two mitochondrial DNA markers, cytochrome oxidase I (COI) and 16S rRNA, and one nuclear marker, 28S rRNA. The results showed a strong genetic structuring among Macaronesia populations, with each island tending to have unique or exclusive haplotypes, though some sharing occurred between islands. We found significant genetic divergence between the population from Cabo Verde and the other sampled population, suggesting that P. rudis is not monotypic, but may include several cryptic species. Bayesian and maximum-likelihood phylogenetic analysis, including all Pinnidae species, indicated that P. rudis from Gorée Island (Senegal) and Baía das Gatas (São Vicente Island) might be undergoing speciation. The high genetic structure found for P. rudis could be influenced by hydrodynamic barriers, local currents and hydrographic isolation, in association with the short larval duration (planktotrophic) reported for this species. Altogether, our findings highlight significant genetic divergence in P. rudis populations, possibly supporting speciation events in the Cabo Verde archipelago among widely distributed taxonomic groups.
Keywords: Pinna rudis; Cabo Verde; Genetic analysis; mtDNA; nDNA; Macaronesia